Method for eliminating coarse beta-Mg17Al12 phase of as-cast AZ91D magnesium alloy

Through the electrical pulse treatment method, the problems of high cost and low efficiency of traditional homogenized annealing treatment are solved, and the refinement and mechanical properties of β-Mg17Al12 phase in cast AZ91D magnesium alloy are achieved, and the forming ability and mechanical properties of magnesium alloy are improved.

CN120536840APending Publication Date: 2025-08-26BEIFANG UNIV OF NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410203912.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-23
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Traditional homogenization annealing treatment is costly, long time, and it is easy to cause abnormal growth of metal grains, making it difficult to effectively eliminate the coarse β-Mg17Al12 phase in cast AZ91D magnesium alloy, affecting the forming ability and mechanical properties of the magnesium alloy.

Method used

Electric pulse treatment methods are adopted, including annealing and electrical pulse processes, with an annealing temperature of 400℃, air-cooled after insulation for 3h to 8h, electric pulse frequency is 500Hz, output voltage is 200V to 400V, and pulse action time is 10min. It is combined with pretreatment and electrode polishing to ensure conductivity.

Benefits of technology

Electric pulse treatment effectively refines the β-Mg17Al12 phase, improving the structural uniformity and mechanical properties of magnesium alloys, making it more efficient, environmentally friendly and energy-saving than traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004712385590000031
    Figure BDA0004712385590000031
  • Figure HDA0004712385600000011
    Figure HDA0004712385600000011
  • Figure HDA0004712385600000012
    Figure HDA0004712385600000012
Patent Text Reader

Abstract

The invention provides a method for eliminating a thick beta-Mg17Al12 phase of an as-cast AZ91D magnesium alloy, which comprises the following steps of: performing complete annealing treatment on the as-cast AZ91D magnesium alloy according to an annealing system that the as-cast AZ91D magnesium alloy is heated to 400 DEG C, air-cooled after heat preservation for 3 hours, and subjected to electric pulse treatment after the annealing treatment is completed, clamping the strip-shaped as-cast AZ91D magnesium alloy on a copper electrode of a high-power pulse power supply, and performing electric pulse treatment, the pulse width intermediate value of the selected pulse power supply is 50 [mu] m, the frequency is 500 Hz, the output voltage value is 200-400 V, and the pulse action time is 10 min. According to the method, electric pulse treatment is utilized, compared with traditional homogenizing annealing treatment, the electric pulse technology is more efficient, more environmentally friendly and more energy-saving, the tissue structure of the magnesium alloy can be effectively improved through electric pulse treatment, the beta-Mg17Al12 phase is refined, and the tissue uniformity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of magnesium alloy material processing technology, specifically a method for eliminating coarse β-Mg 17 Al 12 Phase method. Background Art

[0002] Magnesium alloy has a close-packed hexagonal structure and is difficult to form at room temperature. At the same time, its strength is significantly lower than that of steel and aluminum, which seriously restricts its application in industry. AZ91D magnesium alloy uses the traditional casting process. Under industrial casting conditions, it is a non-equilibrium solidification process. The obtained alloy structure has serious segregation and coarse β-Mg 17 Al 12 The distribution of β-Mg phase along the grain boundaries seriously restricts the forming ability of magnesium alloys. In industry, 420℃ / 8h homogenization annealing treatment is usually used to eliminate the coarse β-Mg 17 Al 12 phase, while homogenization annealing treatment has the disadvantages of high cost, long processing time, abnormal growth of metal grains and easy overburning. Summary of the Invention

[0003] In view of the above problems, the present application provides a method for eliminating the coarse β-Mg 17 Al 12 The method of phase, using electric pulse treatment, is more efficient, environmentally friendly and energy-saving than traditional homogenization annealing. Electric pulse treatment can effectively improve the microstructure of magnesium alloys and refine β-Mg 17 Al 12 phase, improve the uniformity of the organization, and thus improve its mechanical properties.

[0004] In order to achieve the above objectives, this application provides the following technical solutions:

[0005] A novel method for eliminating coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 The method of the present invention is characterized by comprising:

[0006] Annealing treatment: The as-cast AZ91D magnesium alloy was fully annealed. The annealing process was as follows: heating to 400°C, keeping at this temperature for 3 to 8 hours, and then air cooling.

[0007] Electric pulse treatment: The strip cast AZ91D magnesium alloy was clamped on the copper electrode of a high-power pulse power supply for electric pulse treatment. The pulse power supply pulse width was selected to have an intermediate value of 50 μm, a frequency of 500 Hz, an output voltage of 200 V to 400 V, and a pulse action time of 10 min.

[0008] Before the electric pulse treatment, the strip cast AZ91D magnesium alloy after annealing is pretreated. The pretreatment process includes:

[0009] The as-cast AZ91D magnesium alloy was cut into experimental plates with the specifications of 60 mm × 10 mm × 10 mm in length × width × height using a wire-cut EDM machine.

[0010] The processed samples were polished with 400#, 600#, 800#, and 1000# sandpaper in sequence to make them smooth without deep scratches on the surface, and then ultrasonically cleaned in ethanol for 10 min.

[0011] The electrode clamping end of the high-power pulse power supply was polished clean with 600# sandpaper to ensure good conductivity between the sample and the copper electrode.

[0012] In a preferred solution, the electric pulse treatment selects a pulse power supply with a pulse width median value of 50 μm, a frequency of 500 Hz, an output voltage value of 200 V, and a pulse action time of 10 minutes.

[0013] In a preferred solution, the annealing step is: performing complete annealing on the as-cast AZ91D magnesium alloy, and the annealing system is: heating to 400° C., keeping warm for 3 hours and then air cooling.

[0014] In a preferred solution, the annealing step is: fully annealing the as-cast AZ91D magnesium alloy, and the annealing system is: heating to 400°C, keeping warm for 8 hours and then air cooling.

[0015] The beneficial effects of this application are:

[0016] This application uses electric pulse treatment. Compared with the traditional homogenization annealing process, electric pulse technology is more efficient, environmentally friendly and energy-saving. Electric pulse treatment can effectively improve the organizational structure of magnesium alloys and refine β-Mg 17 Al 12 phase, improving tissue uniformity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 SEM images of as-cast AZ91D magnesium alloy at different output voltages;

[0018] Figure 2 The distribution pole figure of the cross section of the as-cast AZ91D magnesium alloy under different output voltages;

[0019] Figure 3 IPF diagram of the cross section of as-cast AZ91D magnesium alloy under different output voltages;

[0020] Figure 4 SEM images of as-cast AZ91D magnesium alloy under different process conditions;

[0021] Figure 5 for Figure 4 SEM area magnification of microstructure;

[0022] Figure 6 for Figure 5 EDS energy spectrum point analysis results;

[0023] Figure 7 The β-Mg in as-cast AZ91D magnesium alloy under different process conditions 17 Al 12 Phase average tensile strength and average elongation. DETAILED DESCRIPTION

[0024] The following will be combined with the Figures 1 to 7 The following embodiments of the technical solution of the present application are described in detail. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only used as examples and are not intended to limit the scope of protection of the present application.

[0025] A novel method for eliminating coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 Phase methods include:

[0026] Annealing treatment: The as-cast AZ91D magnesium alloy was fully annealed. The annealing process was as follows: heating to 400°C, keeping at this temperature for 3 to 8 hours, and then air cooling.

[0027] The strip cast AZ91D magnesium alloy after annealing is pretreated. The pretreatment process includes:

[0028] The as-cast AZ91D magnesium alloy was cut into experimental plates with the specifications of 60 mm × 10 mm × 10 mm in length × width × height using a wire-cut EDM machine.

[0029] The processed samples were polished with 400#, 600#, 800#, and 1000# sandpaper in sequence to make them smooth without deep scratches on the surface, and then ultrasonically cleaned in ethanol for 10 min.

[0030] The electrode clamping end of the high-power pulse power supply was polished clean with 600# sandpaper to ensure good conductivity between the sample and the copper electrode.

[0031] Electric pulse treatment: The strip cast AZ91D magnesium alloy was clamped on the copper electrode of a high-power pulse power supply for electric pulse treatment. The pulse power supply pulse width was selected to have an intermediate value of 50 μm, a frequency of 500 Hz, an output voltage of 200 V to 400 V, and a pulse action time of 10 min.

[0032] The technical effects of the present invention are described below through specific embodiments.

[0033] Example 1:

[0034] A novel method for eliminating coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 Phase method, the main components of the cast AZ91D magnesium alloy are shown in Table 1.

[0035] Table 1 Main components of as-cast AZ91D magnesium alloy

[0036]

[0037] Elimination of coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 The methods specifically include:

[0038] Annealing treatment: The as-cast AZ91D magnesium alloy was fully annealed. The annealing process was as follows: heating to 400°C, holding for 3 hours, and then air cooling.

[0039] The strip cast AZ91D magnesium alloy after annealing is pretreated. The pretreatment process includes:

[0040] The as-cast AZ91D magnesium alloy was cut into experimental plates with the specifications of 60 mm × 10 mm × 10 mm in length × width × height using a wire-cut EDM machine.

[0041] The processed samples were polished with 400#, 600#, 800#, and 1000# sandpaper in sequence to make them smooth without deep scratches on the surface, and then ultrasonically cleaned in ethanol for 10 min.

[0042] The electrode clamping end of the high-power pulse power supply was polished clean with 600# sandpaper to ensure good conductivity between the sample and the copper electrode.

[0043] Electric pulse treatment: The strip cast AZ91D magnesium alloy was clamped on the copper electrode of a high-power pulse power supply for electric pulse treatment. The pulse width of the pulse power supply was selected to have an intermediate value of 50 μm, a frequency of 500 Hz, an output voltage of 200 V, and a pulse action time of 10 min.

[0044] Example 2

[0045] A novel method for eliminating coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 Phase method, the main components of the cast AZ91D magnesium alloy are shown in Table 1.

[0046] Elimination of coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 The methods specifically include:

[0047] Annealing treatment: The as-cast AZ91D magnesium alloy was fully annealed. The annealing process was as follows: heating to 400°C, holding for 3 hours, and then air cooling.

[0048] The strip cast AZ91D magnesium alloy after annealing is pretreated. The pretreatment process includes:

[0049] The as-cast AZ91D magnesium alloy was cut into experimental plates with the specifications of 60 mm × 10 mm × 10 mm in length × width × height using a wire-cut EDM machine.

[0050] The processed samples were polished with 400#, 600#, 800#, and 1000# sandpaper in sequence to make them smooth without deep scratches on the surface, and then ultrasonically cleaned in ethanol for 10 min.

[0051] The electrode clamping end of the high-power pulse power supply was polished clean with 600# sandpaper to ensure good conductivity between the sample and the copper electrode.

[0052] Electric pulse treatment: The strip cast AZ91D magnesium alloy was clamped on the copper electrode of a high-power pulse power supply for electric pulse treatment. The pulse power supply pulse width was selected to have an intermediate value of 50 μm, a frequency of 500 Hz, an output voltage of 400 V, and a pulse action time of 10 min.

[0053] Example 3

[0054] A novel method for eliminating coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 Phase method, the main components of the cast AZ91D magnesium alloy are shown in Table 1.

[0055] Elimination of coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 The methods specifically include:

[0056] Annealing treatment: The as-cast AZ91D magnesium alloy was fully annealed. The annealing process was as follows: heating to 400°C, holding for 8 hours, and then air cooling.

[0057] The strip cast AZ91D magnesium alloy after annealing is pretreated. The pretreatment process includes:

[0058] The as-cast AZ91D magnesium alloy was cut into experimental plates with the specifications of 60 mm × 10 mm × 10 mm in length × width × height using a wire-cut EDM machine.

[0059] The processed samples were polished with 400#, 600#, 800#, and 1000# sandpaper in sequence to make them smooth without deep scratches on the surface, and then ultrasonically cleaned in ethanol for 10 min.

[0060] The electrode clamping end of the high-power pulse power supply was polished clean with 600# sandpaper to ensure good conductivity between the sample and the copper electrode.

[0061] Electric pulse treatment: The strip cast AZ91D magnesium alloy was clamped on the copper electrode of a high-power pulse power supply for electric pulse treatment. The pulse width of the pulse power supply was selected to have an intermediate value of 50 μm, a frequency of 500 Hz, an output voltage of 200 V, and a pulse action time of 10 min.

[0062] Comparative Example 1

[0063] Annealing treatment: The as-cast AZ91D magnesium alloy was fully annealed. The annealing process was as follows: heating to 400°C, holding for 3 hours, and then air cooling.

[0064] Homogenization annealing treatment:

[0065] The as-cast AZ91D magnesium alloy was cut into experimental plates with dimensions of 60 mm × 10 mm × 10 mm (length × width × height) using a wire-cut electric discharge machine. The processed specimens were polished with 400# sandpaper to remove the oxide layer and ultrasonically cleaned in ethanol for 10 min to remove impurities such as oil.

[0066] The treated cast AZ91D magnesium alloy was placed in an alumina crucible and covered with a magnesium alloy cover to prevent oxidation. After completing the above steps, the sample was placed in a box-type resistance furnace for homogenization annealing at 420℃ / 8h.

[0067] Material performance analysis:

[0068] The material properties of the samples obtained in Example 1, Example 2, Example 3 and Comparative Example 1 were analyzed.

[0069] (1) A comparative analysis of the microstructure and mechanical properties of the as-cast AZ91D magnesium alloys of Example 1 and Example 2 and the samples after electric pulse treatment was conducted. The results showed that:

[0070] like Figure 1 SEM images of as-cast AZ91D magnesium alloy under different output voltages at a frequency of 500 Hz.

[0071] like Figure 1 a,β-Mg 17 Al 12 The phase exists in the matrix structure α-Mg in the form of agglomerated large blocks;

[0072] like Figure 1 b, Example 1, when the output voltage is 200V, β-Mg 17 Al 12 The massive structure of the phase completely disappears, and the large flakes gradually dissolve in the α-Mg matrix and transform into dispersed worm strips;

[0073] like Figure 1 c, Example 2, when the output voltage is 400V, β-Mg 17 Al 12 They are connected to each other to form a network structure.

[0074] The matrix structure α-Mg, Example 1, Example 2 β-Mg 17 Al 12 The statistical analysis of the proportion found that: β-Mg 17 Al 12 The contents of the phases are 14.4%, 7.6% and 13.3% respectively.

[0075] Figure 2 、 Figure 3 The distribution pole figure and IPF diagram of the cross section of the as-cast AZ91D magnesium alloy under different output voltages of Example 1 and Example 2 are shown in FIG. 2 and FIG. Figure 3 In the figure, a is untreated, b is Example 1 at 200 V, and c is Example 2 at 400 V. Compared to the original sample without electric pulse treatment, in Example 1, when the output voltage was 200 V, the texture strength of the as-cast AZ91D magnesium alloy on the {0001} basal plane decreased from 114.28 to 25.48, and the grain size of the sample was significantly refined. In Example 2, when the output voltage was 400 V, the texture strength increased to 44.62, and the grain size grew.

[0076] In Example 1, when the output voltage was 200 V, the tensile strength and elongation of the sample reached their maximum values, which were 141.9 MPa and 9.2%, respectively, which were 34.0% and 47.8% higher than those of the original sample without electric pulse treatment (93.7 MPa and 4.8%).

[0077] When the output voltage of Example 2 is 400V, the tensile strength and elongation both drop to 108.3 MPa and 7.3%.

[0078] A comparative analysis of the microstructure and mechanical properties of the as-cast AZ91D magnesium alloy samples was conducted, including the sample of Example 1 that was homogenized at 420°C for 3 hours and then subjected to an electric pulse treatment at a pulse frequency of 500 Hz and an output voltage of 200 V, and the sample of Comparative Example 1 that was homogenized at 420°C for 8 hours and then subjected to an electric pulse treatment.

[0079] like Figure 4 SEM images of as-cast AZ91D magnesium alloy under different process conditions. Figure 4 a, It can be seen from the SEM image of the untreated original cast AZ91D magnesium alloy sample that β-Mg 17 Al 12The phase is distributed in the matrix structure α-Mg in the form of large flakes;

[0080] like Figure 4 b, Sample of Example 1 after homogenization annealing at 420℃ / 3h, large flake β-Mg 17 Al 12 The phase begins to break into a small area of ​​network structure, and the distribution becomes uniform, but there are still small pieces of flakes, such as Figure 4 c, In the sample treated with electric pulse, β-Mg 17 Al 12 The phase is refined into tiny worm-like shapes and the distribution is more uniform;

[0081] like Figure 4 d, in the sample of comparative example 1, which was homogenized at 420℃ for 8h and then subjected to electric pulse treatment, β-Mg 17 Al 12 The phase reprecipitates and begins to reconnect into a network, and β-Mg 17 Al 12 Discontinuous point-like and lamellar precipitation phases precipitate around the phase;

[0082] Figure 5 a is Figure 4 In the enlarged image of area A in d, it can be seen that the precipitated phase is distributed on the matrix in the form of small diamonds and rods. Figure 5 b is Figure 4 In the enlarged image of area B in d, it can be seen that the precipitated phase is in the form of radial lamellae.

[0083] right Figure 5 The precipitated phase Point1 and Point2 in Figures a and b were subjected to EDS point scanning energy spectrum analysis. The analysis results are as follows Figure 6 As shown in a and b, it can be seen that the precipitated phases are all β-Mg 17 Al 12 Mutually.

[0084] Figure 7 The tensile strength and elongation of cast AZ91D magnesium alloy samples after different processing steps.

[0085] in, Figure 7 A is the original sample, i.e., in Examples 1 and 2, annealing treatment: the as-cast AZ91D magnesium alloy was fully annealed, and the annealing system was as follows: heating to 400°C, holding for 3 hours, and then air-cooling the sample;

[0086] Figure 7 B is the sample after homogenization annealing treatment, i.e., the sample obtained in Comparative Example 1;

[0087] Figure 7 C is the sample after electric pulse treatment, i.e. the sample obtained in Example 1

[0088] Figure 7 D is the sample treated with electric pulses after homogenization annealing, i.e., the sample obtained in Example 3;

[0089] Figure 7 The average tensile strength of the untreated as-cast specimen A was 93.7 MPa, and the elongation was 4.8%;

[0090] Figure 7 B. The average tensile strength of the sample of Comparative Example 1 after homogenization annealing at 420°C for 8 hours was 125.0 MPa, and the elongation was 8.5%;

[0091] Figure 7 C, the tensile strength of the sample treated with electric pulses in Example 1 is 141.9 MPa, and the elongation is 9.2%;

[0092] Figure 7 D. After homogenization annealing at 420°C for 8 hours and then electric pulse treatment, the tensile strength and elongation of the sample in Example 3 began to decrease, reaching 114.4 MPa and 8.2% respectively.

[0093] Through the above comparative analysis, it can be seen that the tensile strength and elongation of the cast AZ91D magnesium alloy treated with electric pulses are the highest.

[0094] In summary, the electric pulse treatment process can replace the homogenization annealing process before rolling, and compared with the homogenization annealing process, the electric pulse treatment can make the β-Mg 17 Al 12 Phase refinement and dissolution are more complete; the sample after homogenization annealing and then electric pulse treatment cannot further refine β-Mg 17 Al 12 phase, but will cause it to precipitate in large quantities in the form of diamond rods.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method to eliminate coarse β-Mg in cast AZ91D magnesium alloy 17 Al 12 Phase method, characterized in that include: Annealing treatment: The as-cast AZ91D magnesium alloy was fully annealed. The annealing process was as follows: heating to 400°C, keeping at this temperature for 3 to 8 hours, and then air cooling. Electric pulse treatment: The strip cast AZ91D magnesium alloy was clamped on the copper electrode of a high-power pulse power supply for electric pulse treatment. The pulse power supply pulse width was selected to have an intermediate value of 50 μm, a frequency of 500 Hz, an output voltage of 200 V to 400 V, and a pulse action time of 10 min.

2. The method according to claim 1, characterized in that Before the electric pulse treatment, the strip cast AZ91D magnesium alloy after annealing is pretreated. The pretreatment process includes: The as-cast AZ91D magnesium alloy was cut into experimental plates with the specifications of 60 mm × 10 mm × 10 mm in length × width × height using a wire-cut EDM machine. The processed samples were polished smooth with 400#, 600#, 800#, and 1000# sandpaper in sequence, and ultrasonically cleaned in ethanol for 10 min; The electrode clamping end of the high-power pulse power supply was polished clean with 600# sandpaper to ensure good conductivity between the sample and the copper electrode.

3. The method according to claim 1, characterized in that The electric pulse treatment selected a pulse power supply with a pulse width median value of 50 μm, a frequency of 500 Hz, an output voltage value of 200 V, and a pulse action time of 10 minutes.

4. The method according to claim 1, wherein The annealing treatment step is: performing complete annealing treatment on the cast AZ91D magnesium alloy, and the annealing system is: heating to 400° C., keeping warm for 3 hours and then air cooling.

5. The method according to claim 1, wherein The annealing treatment step is: performing complete annealing treatment on the cast AZ91D magnesium alloy, and the annealing system is: heating to 400° C., keeping warm for 8 hours and then air cooling.